An Investigation of Interconnection between Business Excellence Models and Corporate Sustainability Approach - Adamek, Pavel (European Journal of Sustainable Development, 2018)
The paper provides a general approach to explore the suitability of business excellence models (BEMs) to include corporate sustainability (CS) and on examples of awarded organizations in national quality awards (NQAs) found the synergic approach in deploying issues of BEMs and sustainability. The aim of the paper is to provide an overview of the BEMs approach in the Czech Republic and found the relevance with the issues of corporate sustainability. As an example was involved the Czech organizations awarded in NQAs in the area of excellence and sustainability in 2016. Based on a reflection of the current situation, there is a clear lack of organizations’ approach to principles or strategic management tools that are suitable for implementation to enhance organization excellence including corporate sustainability. Then, an analysis is deployed in order to identify common synergy between BEMs and issues of corporate sustainability. This study is based on information gathered through an extensive literature review using print media and research databases like Emerald, EBSCO, Pro-Quest and we also employed the available sustainable reporting for awarded companies. The study is expected to help in reviewing national business excellence strategies and overview of the collected samples of organizations may help other entities to effectively process reports to use of the synergy of the criteria of the BEMs and corporate sustainability within the relevant NQAs or to target on appropriate stakeholders. Keywords: corporate sustainability, business excellence models, National Quality Awards, EFQM excellence model